2023
DOI: 10.1002/aelm.202201047
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Wide‐Range Flexible Hydrogen Sensor Based on Pd Nanoparticles Decorated Ultrathin SnO2 Film

Abstract: Highly sensitive and reliable hydrogen detection is prerequisite for the large‐scale implementation of green energy hydrogen. It remains a tough challenge to get a highly selective H2 sensor to low concentration H2 gas with low working temperature. In this work, high performance flexible hydrogen sensor using ultrathin SnO2 film decorated by Pd nanoparticles (NPs) on polyimide (PI) was developed based on versatile atomic layer deposition (ALD) and cluster beam deposition (CBD). The influence of Pd NPs loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…24,25 The 2D electrical transportation behaviors are dominated by grain boundaries, which lead to an inefficient signal transduction from the surface chemical process to the bulk conductivity. Various new studies have been reported in the literature to enhance the gas reception and transduction performance of the SnO 2 -based ultrathin films, e.g., by doping, 26 noble metal decoration, 27 and UV illumination. 28 However, there is still a general lack of effective strategies to enhance the intrinsic sensing performance of the SnO 2 -based films, which is a major obstacle to their further performance optimization and practical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 The 2D electrical transportation behaviors are dominated by grain boundaries, which lead to an inefficient signal transduction from the surface chemical process to the bulk conductivity. Various new studies have been reported in the literature to enhance the gas reception and transduction performance of the SnO 2 -based ultrathin films, e.g., by doping, 26 noble metal decoration, 27 and UV illumination. 28 However, there is still a general lack of effective strategies to enhance the intrinsic sensing performance of the SnO 2 -based films, which is a major obstacle to their further performance optimization and practical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the defective (101) surfaces of the ultrathin SnO 2 can be steadily passivated by the undesirable surface adsorbents (mostly the OH groups) under ambient conditions. The OH groups will dominate the surface electron states and hinder the gas–solid interaction, leading to unsatisfied gas sensing performance. , Besides that, the majority of the nanocrystalline 2D oxides consist of numerous nanograins with in-plane grain sizes down to a few nanometers. , The 2D electrical transportation behaviors are dominated by grain boundaries, which lead to an inefficient signal transduction from the surface chemical process to the bulk conductivity. Various new studies have been reported in the literature to enhance the gas reception and transduction performance of the SnO 2 -based ultrathin films, e.g., by doping, noble metal decoration, and UV illumination . However, there is still a general lack of effective strategies to enhance the intrinsic sensing performance of the SnO 2 -based films, which is a major obstacle to their further performance optimization and practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 However, this expansion and contraction of the lattice during hydrogenation and dehydrogenation can make Pd vulnerable to both mechanical and structural instability. 28,29 To address these challenges, blending Pd with other noble metals is being explored as a promising solution. When compared to single-metal counterparts, Pd alloy catalysts exhibit increased stability, tunability, and a synergistic effect, making them valuable in gas sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Redox reactions between the target gas and chemisorbed oxygen species are the mechanism of sensing . Fabrication of nanostructured MOS materials with a high specific surface area has proved to be an effective strategy to promote gas adsorption for enhanced sensing performance. , Alternatively, noble metal particles (such as Pt, , Pd, Rh, and Au) are extensively utilized as catalysts to optimize the sensing performance of MOS sensors due to their remarkable electronic and catalytic activity. Noble metal industrial applications in chemical sensors are, however, severely limited by their high cost.…”
mentioning
confidence: 99%